Intranasal Scope Negotiation Trajectories for Flexible Nasopharyngolaryngoscopy - Vijay Bidkar; Kalaiselvi Selvaraj; Amrusha Raipure; Sandeep Dabhekar; Kiran Kumar Prathipati; Lisha Sarode (Journal of Rhinology)
Background and Objectives Flexible nasopharyngolaryngoscopy (F-NPLS) is a routine procedure performed in office settings. We compared two different intranasal scope navigation techniques used during F-NPLS, evaluating patient comfort and practitioner satisfaction. Methods This is a prospective, randomized, parallel-group controlled study. Patients undergoing F-NPLS to evaluate the upper airway were enrolled and randomized into two study groups. Patients in group A underwent intranasal scope negotiation following a trajectory below the middle turbinate; for group B, a trajectory along the inferior turbinate was used. The primary outcome evaluated was the successful, unhindered negotiation of the scope on the first attempt. Secondary outcomes included patient-perceived pain, incidents of mucosal trauma and bleeding, and the frequency and necessity of repeat scopy. Results In total, 111 patients were randomized into group A (n=53) and group B (n=58). Baseline characteristics, such as age and sex, were similar in both groups. There was no statistically significant difference between the groups with respect to the primary outcome (group A: 52.8% vs. group B: 55.2%, p=0.8). The frequency of F-NPLS without episodes of mucosal trauma was significantly higher in group B (group A: 56.9% vs. group B: 35.9%, p=0.004). Mucosal ecchymosis was a common finding in group A (group A: 41.5% vs. group B: 13.8%, p=0.03), while nasal bleeding was more frequently observed in group B, although the difference was not statistically significant (group A: 29.3% vs. group B: 22.6%, p=0.42). Conclusion The present study demonstrated that the success rate of unhindered F-NPLS was comparable between the two trajectories. However, patients experienced moderate to severe pain during repeat scopy compared to the initial F-NPLS attempt.